Assessment of Creative Thinking Skills through Imitation, Modification, and Construction of Creative Thinking Models - Fitriyyah, Aslihatul; Anwar, Lathiful; Hafiizh, Mohammad (PRISMA, 2024)
Creative thinking is an ability that must be possessed by every student being capable of resolving issues in various ways that are right. Creative thinking is one of the goals of education that has become a concern in recent years. But the facts show that the ability to think creatively is still low. The main thing that educators do is to identify the level of creative thinking of students so that educators know which students ' creative thinking skills need to be improved. Until now, the ability of educators in developing creative thinking ability tests is still low due to the lack of training and guidance that focuses on improving creative thinking skills. The aim of this research is to generate a product in the form of a test instrument of creative thinking skills that are valid, practical and effective. This research is a development research conducted with 4D models (Define, Design, Develop, Disseminate), but the disseminate stage is not carried out due to time and cost constraints. The development phase was carried out on 88 students of grade VIII of One of the private high schools in Malang . The development results show that the creative thinking ability test is valid, practical and effective.